1995
DOI: 10.1055/s-2007-1015925
|View full text |Cite
|
Sign up to set email alerts
|

Häufigkeit, Altersabhängigkeit und Geschlechtsverteilung des Fersensporns

Abstract: In 1027 lateral radiograms of the ankle in a Caucasian population, 161 plantar and/or dorsal calcaneal spurs (15.7%) were diagnosed. Plantar spurs were more common than dorsal spurs (11.2 and 9.3% respectively). Prevalence of both spurs increases considerably with the rising age. Dorsal spurs appear slightly earlier than plantar spurs. The spur frequencies are similar in left and right feet. The plantar spurs were significantly (p < 0.0001) more common in women than in men in general, while dorsal spurs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Similar to our results, calcaneal spurs increase with age and tend to be seen more often in women; however, that has not been consistently reported in all studies. 26,33,34,37 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, calcaneal spurs increase with age and tend to be seen more often in women; however, that has not been consistently reported in all studies. 26,33,34,37 …”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] and Riepert et al . [ 8 ] figures of 16% and 11% and 11.2% and 9.3%, respectively. Similarly, Weiss[ 11 ] also found an increased incidence of dorsal spurs.…”
Section: R Esultsmentioning
confidence: 99%
“…Riepert et al . [ 8 ] found that plantar spurs were more common (11.2%), though later to appear as compared with dorsal spurs (9.3%). Bassiouni[ 12 ] found that the frequency of calcaneal spurs rose with age (maximum in 41–60 year of age group) in patients of osteoarthritis and rheumatoid arthritis than controls.…”
Section: R Esultsmentioning
confidence: 99%
“…In the only three large-scale epidemiological studies of Achilles and plantar spurs there are unequal numbers of subjects in the different age cohorts and a lack of adequate representation of older individuals [3,6,7]. Moreover, more women than men are typically recruited in their studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more women than men are typically recruited in their studies. Furthermore, size of the spur has not been adequately addressed [3,6,7]. This information is important in understanding the natural history spur formation and/or regression.…”
Section: Introductionmentioning
confidence: 99%